Study the Toll-like Receptor 2 and Dectin-1 in mice treated with beta‐ glucans and infected with Salmonella Typhimurium - Nidhal R. Mahdi (University of Thi-Qar Journal of Science, 2019)
Objective: Toll-like receptors (TLRs) are essential components for the induction of innate immune responsesin different tissues including the small intestine, spleen and mesenteric lymph nodes. We investigated theexpression of TLR2 in these tissues in mice infected with Salmonella Typhimurium. In this study we haveexamined how dectin-1, a lectin family receptor for β-glucans, collaborates with TLR-2 in recognition ofmicrobes.Methods :In this study two groups of mice were treated with the β- glucan (local and commercial extract)and infected with(1x10 6 CFU/ml) S. Typhimurium at different intervals group 1 at day zero and group 2after seven days of the experiment .The immunohistochemistory assay has been performed to detect TLR-2and dectine-1 in the tissues of small intestine, spleen and mesenteric lymph nodes of the mice; the principle ofthis assay was done according to the manufacturer instructions (U.S.biological) .Results: In the immunohistochemistory assay, positive cells were indicated by cytoplasmic staining and thepercentage of positive in 100 cells was recorded and graded. The grades were 1+ (<25%), 2+ (25-75%) and3+ (>75%). Statistical analysis with Chi- Square tests revealed that there were significant differences (p˂0.05)between groups, also between grades within the same group in the small intestine, spleen with TLR2expression; also we demonstrated the same results with Dectin-1 expression in the small intestine andmesenteric lymph nodes, except in the spleen which showed that there were no any relevant differences (p˂0.05 ) between the groups and the cell- grades within the group itself.Conclusions: The Oral treatment of both soluble β-glucan from Saccharomyces cerevisiae (Local andcommercial extracts) enhanced the host resistance in mice before the infection with S.Typhimurium. Theresults of Immunohistochemical assay showed that the β- glucan also inducted the expression of Dectin-1 andTLR-2 receptors on the cells, and also proved a collaborative reaction between these two receptors.